THE PERFORMANCE MEASUREMENT OF PT. ASURANSI JASA INDONESIA SEMARANG USING BALANCED SCORECARD APPROACH - Tri Astono Arif; Hari Susanta Nugraha; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2014)
PT. Asuransi Jasa Indonesia Semarang is a company focus on loss insurance. All this time the company only seen performance from financial aspect without noticed to non-financial aspect so there discrepancy between two aspects. Balanced Scorecard's  as a performance measurement system that will score company’s performance not only financial but also non-financial too. This research was conducted PT. Asuransi Jasa Indonesia Semarang with balanced scorecard approach to measuring through four perspectives which is financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The purpose of this research was to determine the performance of PT. Asuransi Jasa Indonesia Semarang seen from the balanced scorecard method. The data used is using primary data obtained through observation and FGD (Focus Group Discussion). Beside the primary data, secondary data used in this research such as financial data period of 2010-2012. From the results of measurements that have been done show that financial perspective performance was quite good but still a lot of current assets not yet maximized. Customer perspective performance was quite good during last three years although customer retention and customer acquisition had fluctuating movement. Beside that internal business process performance categorized was enough because still less effective and efficient in perform to operate it. Learning and growth perspective performance was quite good but the company must pay attention to employee productivity that still unstable. Suggestion which can be submitted is PT. Asuransi Jasa Indonesia Semarang must pay more attention to non-financial aspects especially internal business process perspective and learning and growth perspective.